The Effect of Leadership, Work Facilities, Competence, and Motivation on Employee Performance of Ketakasi Fruit Cooperative Jember - Retno Widiyastiwi; Yuniorita Indah Handayani; Muhaimin Dimyati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research analyzes the influence of leadership, work facilities, competence and motivation on the performance of employees of the Ketakasi Fruit Cooperative in Jember. Effective leadership, adequate work facilities, employee competence, and motivation are the main factors that influence productivityThis research used a total population of 69 employees of the Ketakasi Fruit Cooperative in Jember. This research uses a saturated sample method. The results of the research show that leadership, work facilities, competence and work motivation have a significant influence on lecturer performance and together these factors have a significant influence on lecturer performance. From the results, it is concluded that the research emphasizes the importance of competency-based leadership (communication, analysis, decision making) to create a supportive work environment, increase employee motivation and performance. The results can help design more effective leadership development programs. Adequate work facilities increase employee comfort, efficiency and productivity. These findings encourage organizations to improve relevant facilities to create a conducive work environment and reduce turnover rates. Employee competencies (knowledge, skills, attitudes) have a significant influence on performance. Organizations can use these results to develop training that focuses on increasing competency, supporting productivity, and increasing competitiveness. And work motivation has a no direct impact on employee performance. Institutions can leverage these results to design motivation-enhancing programs, such as rewards or recognition, to create a more productive work environment.